Variants in GNAI1 cause a syndrome associated with variable features including developmental delay, seizures, and hypotonia. - Muir, Alison M; Gardner, Jennifer F; van Jaarsveld, Richard H; de Lange, Iris M; van der Smagt, Jasper J; Wilson, Golder N; Dubbs, Holly; Goldberg, Ethan M; Zitano, Lia; Bupp, Caleb; Martinez, Jose; Srour, Myriam; et al. (Genet Med, 2021)
PURPOSE: Neurodevelopmental disorders (NDDs) encompass a spectrum of genetically heterogeneous disorders with features that commonly include developmental delay, intellectual disability, and autism spectrum disorders. We sought to delineate the molecular and phenotypic spectrum of a novel neurodevelopmental disorder caused by variants in the GNAI1 gene. METHODS: Through large cohort trio-based exome sequencing and international data-sharing, we identified 24 unrelated individuals with NDD phenotypes and a variant in GNAI1, which encodes the inhibitory Gαi1 subunit of heterotrimeric G-proteins. We collected detailed genotype and phenotype information for each affected individual. RESULTS: We identified 16 unique variants in GNAI1 in 24 affected individuals; 23 occurred de novo and 1 was inherited from a mosaic parent. Most affected individuals have a severe neurodevelopmental disorder. Core features include global developmental delay, intellectual disability, hypotonia, and epilepsy. CONCLUSION: This collaboration establishes GNAI1 variants as a cause of NDDs. GNAI1-related NDD is most often characterized by severe to profound delays, hypotonia, epilepsy that ranges from self-limiting to intractable, behavior problems, and variable mild dysmorphic features.
Keywords: Child; Developmental Disabilities; Humans; Intellectual Disability; Muscle Hypotonia; Neurodevelopmental Disorders; Seizures; Whole Exome Sequencing

Pathogenic Variants in CEP85L Cause Sporadic and Familial Posterior Predominant Lissencephaly. - Tsai, Meng-Han; Muir, Alison M; Wang, Won-Jing; Kang, Yi-Ning; Yang, Kun-Chuan; Chao, Nian-Hsin; Wu, Mei-Feng; Chang, Ying-Chao; Porter, Brenda E; Jansen, Laura A; Sebire, Guillaume; Deconinck, Nicolas; et al. (Neuron, 2020)
Lissencephaly (LIS), denoting a "smooth brain," is characterized by the absence of normal cerebral convolutions with abnormalities of cortical thickness. Pathogenic variants in over 20 genes are associated with LIS. The majority of posterior predominant LIS is caused by pathogenic variants in LIS1 (also known as PAFAH1B1), although a significant fraction remains without a known genetic etiology. We now implicate CEP85L as an important cause of posterior predominant LIS, identifying 13 individuals with rare, heterozygous CEP85L variants, including 2 families with autosomal dominant inheritance. We show that CEP85L is a centrosome protein localizing to the pericentriolar material, and knockdown of Cep85l causes a neuronal migration defect in mice. LIS1 also localizes to the centrosome, suggesting that this organelle is key to the mechanism of posterior predominant LIS.
Keywords: Adolescent; Adult; Age of Onset; Animals; Centrosome; Child; Child, Preschool; Chromosome Aberrations; Classical Lissencephalies and Subcortical Band Heterotopias; Cytoskeletal Proteins; Female; Gene Knockdown Techniques; Genetic Variation; Heterozygote; Humans; Infant; Magnetic Resonance Imaging; Male; Mice; Mutation; Oncogene Proteins, Fusion; Pedigree; Seizures; Young Adult

Disruptive mutations in TANC2 define a neurodevelopmental syndrome associated with psychiatric disorders. - Guo, Hui; Bettella, Elisa; Marcogliese, Paul C; Zhao, Rongjuan; Andrews, Jonathan C; Nowakowski, Tomasz J; Gillentine, Madelyn A; Hoekzema, Kendra; Wang, Tianyun; Wu, Huidan; Jangam, Sharayu; Liu, Cenying; et al. (Nat Commun, 2019)
Postsynaptic density (PSD) proteins have been implicated in the pathophysiology of neurodevelopmental and psychiatric disorders. Here, we present detailed clinical and genetic data for 20 patients with likely gene-disrupting mutations in TANC2-whose protein product interacts with multiple PSD proteins. Pediatric patients with disruptive mutations present with autism, intellectual disability, and delayed language and motor development. In addition to a variable degree of epilepsy and facial dysmorphism, we observe a pattern of more complex psychiatric dysfunction or behavioral problems in adult probands or carrier parents. Although this observation requires replication to establish statistical significance, it also suggests that mutations in this gene are associated with a variety of neuropsychiatric disorders consistent with its postsynaptic function. We find that TANC2 is expressed broadly in the human developing brain, especially in excitatory neurons and glial cells, but shows a more restricted pattern in Drosophila glial cells where its disruption affects behavioral outcomes.

ZMIZ1 Variants Cause a Syndromic Neurodevelopmental Disorder. - Carapito, Raphael; Ivanova, Ekaterina L; Morlon, Aurore; Meng, Linyan; Molitor, Anne; Erdmann, Eva; Kieffer, Bruno; Pichot, Angélique; Naegely, Lydie; Kolmer, Aline; Paul, Nicodème; Hanauer, Antoine; et al. (Am J Hum Genet, 2019)
ZMIZ1 is a coactivator of several transcription factors, including p53, the androgen receptor, and NOTCH1. Here, we report 19 subjects with intellectual disability and developmental delay carrying variants in ZMIZ1. The associated features include growth failure, feeding difficulties, microcephaly, facial dysmorphism, and various other congenital malformations. Of these 19, 14 unrelated subjects carried de novo heterozygous single-nucleotide variants (SNVs) or single-base insertions/deletions, 3 siblings harbored a heterozygous single-base insertion, and 2 subjects had a balanced translocation disrupting ZMIZ1 or involving a regulatory region of ZMIZ1. In total, we identified 13 point mutations that affect key protein regions, including a SUMO acceptor site, a central disordered alanine-rich motif, a proline-rich domain, and a transactivation domain. All identified variants were absent from all available exome and genome databases. In vitro, ZMIZ1 showed impaired coactivation of the androgen receptor. In vivo, overexpression of ZMIZ1 mutant alleles in developing mouse brains using in utero electroporation resulted in abnormal pyramidal neuron morphology, polarization, and positioning, underscoring the importance of ZMIZ1 in neural development and supporting mutations in ZMIZ1 as the cause of a rare neurodevelopmental syndrome.
Keywords: Alleles; Animals; Child; Child, Preschool; Developmental Disabilities; Female; Humans; Infant; Intellectual Disability; Male; Mice; Point Mutation; Syndrome; Transcription Factors